2012
DOI: 10.1073/pnas.1207587109
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence of a new catalytic intermediate in the pathway of ATP hydrolysis by F 1 –ATPase from bovine heart mitochondria

Abstract: The molecular description of the mechanism of F 1 -ATPase is based mainly on high-resolution structures of the enzyme from mitochondria, coupled with direct observations of rotation in bacterial enzymes. During hydrolysis of ATP, the rotor turns counterclockwise (as viewed from the membrane domain of the intact enzyme) in 120°steps. Because the rotor is asymmetric, at any moment the three catalytic sites are at different points in the catalytic cycle. In a "ground-state" structure of the bovine enzyme, one sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 32 publications
9
98
0
Order By: Relevance
“…In structures of bovine F 1 -ATPase, the β E -subunit is occupied by an ADP molecule, and no magnesium ion, when crystals were grown in the presence of the magnesium chelator phosphonate (33) (Fig. 4C), and the phosphate analog thiophosphate (34) occupies a similar position to the phosphate in the current structures (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In structures of bovine F 1 -ATPase, the β E -subunit is occupied by an ADP molecule, and no magnesium ion, when crystals were grown in the presence of the magnesium chelator phosphonate (33) (Fig. 4C), and the phosphate analog thiophosphate (34) occupies a similar position to the phosphate in the current structures (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…1C) is 0.91 Å. The higher resolution of the mutant structure revealed that the magnesium ions associated with ADP molecules in the β TP -and β DP -catalytic sites are hexacoordinated by four water molecules, the hydroxyl group of βThr158, and the oxygen atom O2B of the adenosine, as in structures of mitochondrial F 1 -ATPases (5)(6)(7)(30)(31)(32)(33)(34). Also, in the nucleotide-binding domains of the β E -subunits, there was additional density interpreted as a phosphate ion.…”
Section: Resultsmentioning
confidence: 99%
“…Although conformational substeps have been observed structurally for superfamily 1 and 2 helicases and for motors such as the F1 ATPase, myosin, and kinesin (72)(73)(74)(75), similar insights have not been forthcoming for hexameric helicase/translocase systems. Functional substeps (as well as macrosteps) are frequently observed in single-molecule studies of motor proteins (76,77), but the architectural underpinnings of these events often remained unresolved.…”
Section: Structural Snapshots Reveal Translocation Substeps In a Hexamentioning
confidence: 99%
“…These opening/closing and loosening/tightening motions in the αβ-dimer are closely related to chemical reactions, such as nucleotide binding and catalytic events (19,23,(45)(46)(47). For the systematic structural comparison, we selected five representative crystal structures: PDB ID codes 1BMF (4), 1H8E (48), 2JDI (38), 3OAA (41), and 4ASU (49). The 1BMF, 3OAA, and 2JDI structures have already been mentioned.…”
Section: Systematic Analysis Of Crystal Structures Of Atp Waiting Andmentioning
confidence: 99%
“…The 1BMF, 3OAA, and 2JDI structures have already been mentioned. The 1H8E and 4ASU structures are thought to be the catalytic intermediate states, particularly in the product release step (48,49). PCA identified two major axes, principal component 1 (PC1) and PC2, along which the structures can be best separated (Materials and Methods and Fig.…”
Section: Systematic Analysis Of Crystal Structures Of Atp Waiting Andmentioning
confidence: 99%